Publisher Correction: HIV-1 replication complexes accumulate in nuclear speckles and integrate into speckle-associated genomic domains - Ashwanth C. Francis (Nature Portfolio, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-20152-w